Repositioning documentary film in Malaysia: an empirical study of production criteria and practices / Khairulfazi Haji Sa’ari - Sa’ari, Khairulfazi (Institute of Graduate Studies, UiTM, 2015)
During the Malaysia Film Unit (MFU) era, Malaysia was renowned for producing good documentary and was a significant documentary film producer in Asia. The digital revolution has led to a new interest in documentary which has brought about the need for Malaysia to reform and reposition its documentary film production environment. However, despite the various government efforts it is still underdeveloped and its quality is generally considered to be low. This study examined the state of documentary in an effort to ameliorate the current practices of documentary production in Malaysia and, to identify essential criteria that are vital to producing documentary, determine the challenges to the current film makers and to make recommendations as to ways to improve the existing practices. A mixed methodology was utilized. A total of 124 self-administered survey questionnaires were received out of the 198 sent out to active practitioners in the Klang Valley…